Unphosphorylated dimers are not required for the assembly of active STAT1 and STAT3 homo-and heterodimers - Krause, Sebastian C. (2023)
STATs are latent signalling proteins and transcription factors that are activated by phosphorylation upon ligand binding to cytokine receptors. All seven mammalian STATs form dimers upon activation. So far, research focused on homodimers, but it is now recognised that some STATs can also form heterodimers. Yet, it is unclear what determines the formation of individual dimer types, especially when multiple STATs get activated simultaneously. Several STATs assemble inactive, unphosphorylated dimers. However, their structure is different from the active signalling complex. Therefore, it is conceivable that unphosphorylated STAT dimers may regulate the composition of active signalling complexes. This would mean that activated complexes arise from a pre-defined pool of unphosphorylated STAT homo- and heterodimers via a cytokine-induced change in dimer conformation. Alternatively, active signalling complexes may form independent of their unphosphorylated counterparts. This work describes two new cell-based assays and their application with a focus on STAT1 and STAT3, whose capability to form active heterodimers is relatively well characterised, to test these alternatives. Firstly, the Nuclear Translocation Assay is based on the ability of STATs to accumulate inside the nucleus after cytokine treatment. This phenotype is mediated by a nuclear localisation signal (NLS) sequence and can be disrupted by mutation. It was found here that said mutation is dominant-negative for STAT1, STAT3 and STAT5B nuclear import. Therefore, it is possible to assess active dimer formation between an accumulation mutant and another STAT by observing their cytokine-induced nuclear accumulation pattern. If the two proteins form active dimers, cytokine-induced nuclear accumulation of both is diminished. In turn, if they do not form active dimers, cytokine-induced nuclear accumulation is diminished for the mutant but not the other STAT. In the Nuclear Translocation Assay, this effect is made visible in live-cell microscopy by fusing the putative interaction partners with different fluorescent proteins. Testing several STAT1 and STAT3 wild-types and mutants, that disrupt the unphosphorylated but not active dimers, using this assay revealed that active homo- and heterodimers formed independent of their unphosphorylated counterparts. Secondly, the Co-localisation Assay was used to assess the formation of unphosphorylated dimers between different STATs. The assay takes advantage of the observation that unphosphorylated STATs shuttle to and from the nucleus constitutively and that the balance of this can be altered in favour of either the nucleus or cytoplasm by fusion with an external signal sequence. If a certain baitSTAT fusion protein can form latent dimers with a co-expressed test-STAT, then both proteins co-localise in the targeted compartment as visualised by different fluorescent protein tags. If not, then co-localisation is diminished. Applying this to STAT1 and STAT3 revealed that both paralogues readily formed unphosphorylated homodimers but not heterodimers. Overall, the findings from both assays suggest that active STAT1 and STAT3 homo- and heterodimer formation is independent of prior assembly as unphosphorylated dimers. Furthermore, the evidence presented here suggests that their homo- and heterodimers may form at equal rates.